Evaluation of the analgesic and anti-inflammatory activity of fixed dose combination: Non-steroidal anti-inflammatory drugs in experimental animals - Amit Lahoti; Bhupinder S Kalra; Uma Tekur (Wolters Kluwer Medknow Publications, 2014)
Background: In India, a number of fixed dose drug combinations of non-steroidal anti-inflammatory drugs (NSAID's) are available, often as over-the-counter products. These combinations are being prescribed too. Evidence for efficacy of NSIAD fixed dose combination is lacking. Objectives: The current study was undertaken to assess the analgesic and anti-inflammatory efficacy of these combinations over their individual components. Materials and Methods: The study used three NSAIDs viz; paracetamol, ibuprofen and diclofenac sodium, alone or in combination with paracetamol. Animals were divided into six groups with six animals in each group. Analgesic activity was tested by writhing test and paw edema model was used to assess the anti-inflammatory activity. The test drugs were administered orally 30 min prior to injecting 0.6% solution of glacial acetic acid intraperitoneally for writhing test. For paw edema test, after 30 min of drugs administration, animals were injected with 0.1 ml of 1% carrageenan in subplanter region for inducing inflammation. Paw volume was again measured at baseline and after 3 h of subplanter injection of 1% carrageenan. Results: The analgesic and the anti-inflammatory activity of paracetamol and ibuprofen combination were significantly greater than the individual agents when used alone. However, no significant difference in the analgesic or anti-inflammatory activity was found between diclofenac sodium and its combination with paracetamol. It was observed that diclofenac sodium was the most efficacious of the analgesics tested. Combining paracetamol with diclofenac did not show superior analgesic activity compared to diclofenac alone (P = 0.18). Conclusion: Combining paracetamol with ibuprofen enhances analgesic/anti-inflammatory activity over their individual component but potentiation of analgesic activity of diclofenac was not seen when paracetamol was added to it.